The Phenomenon of Murals and Graffiti as Media for Social Criticism in the Perspective of Social Interaction Alfred Schutz - Dwi Setiawan; Djarot Meidi Budi Utomo (Indonesian Journal of Cultural and Community Development, 2022)
The phenomenon of murals and graffiti has existed since time immemorial, the development is very massive in several cities in Indonesia, including the city in Sidoarjo, in Sidoarjo itself there are several points that are being targeted by artists as a form of social criticism media that occurs in the city of Sidoarjo, then from that to find out what motives behind them in drawing about social criticism in the city of Sidoarjo in carrying out social criticism. Sidoarjo. This study uses qualitative research with phenomenological methods, the theory used is Alfred Schutz. This data collection technique uses participant observation, in-depth interviews. and documentation. The results of this study indicate that the motives of these artists depart from their anxiety that they experience in their daily lives. So it's not surprising that they drew on social criticism in Sidoarjo. This also shows that these artists have limitations in the medium of expression in their work in the Public Space Room in Sidoarjo.